"He seemed so normal": Single tactic perpetrators of sexual violence are similar to non-violent men using the DSM-5's hybrid personality disorder model. (1st March 2018) - Norton-Baker, Mara; Russell, Tiffany D.; King, Alan R.
Abstract: The corpus of sexual violence literature contains numerous studies comparing perpetrators to non-perpetrators, but less is known about differences between those using different tactics (i.e., physical/aggressive, non-physical/coercive, or both/polytactic). Similarly, specific personality traits are often measured in sexual violence research, but personality disorder studies are less common. This research addresses these gaps by investigating potential personality disorder diagnoses in aggressive, coercive, and polytactic perpetrators using the DSM-5 's hybrid model of personality disorders. A nationwide sample of adult men ( N  = 672) completed a survey measuring personality traits and sexually violent experiences. Men reporting sexual violence were expected to generate higher levels of maladaptive personality trait scores, leading to higher prevalence rates of Antisocial and Narcissistic Personality Disorders, than non-violent men. Aggressive and coercive men's personality trait scores were statistically similar to those of non-violent men. Polytactic men were significantly more maladaptive than study counterparts, and were at greater risk of being classified as personality disordered. These findings have implications for models predicting sexual violence and for intervention and prevention efforts. Highlights: PID-5 scores of non-violent and single-tactic men were statistically similar. Polytactic men were over 3 × more likely to meet PD criteria than single-tactic men. Nearly 40% of polytactic men were classified as NPD. Polytactic men reported twice as many acts of SV compared to aggressive-only men.